Real time Imaging (Intraoperative Doppler) in Median Arcuate Ligament Syndrome Management: A Case Report - Prem Shah; Haryax Pathak; Bhasha Vaidya (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Median Arcuate Ligament Syndrome (MALS) is a rare cause of chronic abdominal pain due to coeliac trunk compression, typically affecting middle-aged women. Surgical decompression is the gold standard, but technical failure or recurrence poses a significant challenge. The authors report a rare case of recurrent MALS in a 31-year-old male who presented with severe, persistent abdominal pain 1.5 years after an initial laparoscopic ligament release. Preoperative Computed Tomography (CT) and Doppler Ultrasound (DUS) confirmed the recurrence, showing coeliac trunk kinking and a markedly elevated Peak Systolic Velocity (PSV) of 235 cm/sec. Due to dense adhesions from the previous procedure, the patient underwent a re-do surgery via open laparotomy. The key to successful re-operation was the use of intraoperative DUS to precisely localise the coeliac trunk amidst fibrotic tissue. Following complete surgical decompression of the artery, the intraoperative PSV immediately dropped to 80 cm/sec, confirming adequate flow restoration. The patient experienced complete, sustained symptom resolution at the 6-month follow-up. The present case highlights that intraoperative DUS is a vital tool for ensuring the completeness of coeliac axis decompression, especially in complex, re-operative settings where persistent adhesions obscure anatomical planes.